The Design Of Cultural Awareness Development Model Based On Indonesian Culture On Guidance And Counseling Students - Yusri, Fadhilla; Afrida, Yeni; Putri, Erlin Depianti (Counsellia: Jurnal Bimbingan dan Konseling, 2023)
This research was done to create a development model of cultural awareness based on a valid, practical, and effective Indonesian culture to develop students’ cultural awareness as the prospective of counselor. The research is a research and development (R & D) type with the ADDIE approach to develop a valid, practical, and effective model to develop cultural awareness based on Indonesian culture. An accidental sampling technique was used to determine 41 subjects in the study. Data was collected by giving the cultural awareness instrument directly to the sample. Product validity and practicality tests were carried out by 2 competent experts. The Kendall's coefficient test statistic was used to analyze data both descriptively and inferentially. The research produced a model to develop cultural awareness based on Indonesian culture. To develop student’s cultural awareness as the prospective counselor, the research is valid (94.08%), practical (93.112% practicality value), and effective (Asymp. Sig value 0.001). The development model of cultural awareness based on Indonesian culture can be used to develop students’ cultural awareness as the prospective of counselor. Its application can be modified to fit the students' characteristics and cultural background.